National security and double government - Glennon, Michael J., 1947- (New York : Oxford University Press, 2014)
Why has U.S. national security policy scarcely changed from the Bush to the Obama administration? And why does it matter? The theory of 'double government' posed by the 19th century English scholar Walter Bagehot suggests a disquieting answer. The public is encouraged to believe that the presidency, Congress, and the courts make security policy. That belief sustains these institutions' legitimacy. Yet their authority is largely illusory. National security policy is made, instead, by a 'Trumanite network' of several hundred members that is largely concealed from public view.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 24, 2014).
Keywords: National security -- United States -- Management; National security -- United States -- Decision making; Legislative oversight -- United States; Judicial review -- United States; Government accountability -- United States; Politics and Government